Assessment of the Knowledge and Attitude on HIV/AIDS Among Drivers’ Wives - Prajapati, LM; Sanjel, S (Kathmandu University Medical Journal, 2014)
Backgroud It is generally accepted and well-documented that long distance drivers remain one of the key forces in the spread of HIV/AIDS as they are highly mobile and spending long hours on the road away from their families which makes them very likely to use the services of commercial sex workers (CSWs). Objectives To identify the knowledge and attitude among Drivers’ wives on HIV/AIDS. Methods A cross-sectional survey was conducted between August and September 2010 to assess the knowledge and attitude of drivers’ wives on HIV/AIDS in Banepa, Dhulikhel and Panuti Municipalities, Kavre district central Nepal. Using social network sampling technique 248 drivers’ wives were selected. Data were obtained using the structured and semi-structured questionnaire through interview technique. Verbal consent was taken before collecting data. Both descriptive and inferential statistics were computed. Results Ninety six percent of the respondents heard of HIV/ AIDS. Majority (65.7%) of the sources of the information were television followed by radio (56.5%), friends (33.5%), husband (19.4%), newspapers (17.7%) and posters (17.3%). The educational status and economic status of the respondents show significant association. The parameters regarding attitude revealed statistical significant. Conclusion The age and ethnicity of the respondents did not exhibit the association with awareness on HIV/ AIDS whereas, educational status and economic status of the respondents and the parameters regarding attitude revealed statistical show significant association. DOI: http://dx.doi.org/10.3126/kumj.v10i4.10989 Kathmandu Univ Med J 2012;10(4):20-24